Storage stability of fermented milk with probiotic monoculture and transglutaminase - Izabela Dmytrów; Anna Mituniewicz-Małek; Małgorzata Ziarno; Jerzy Balejko (Czech Journal of Food Sciences, 2019)
The effect of microbial transglutaminase on selected physicochemical and organoleptic characteristics and viability of probiotic bacteria in fermented milk inoculated with probiotic monoculture (Lactobacillus acidophilus LA 5 or Bifidobacterium bifidum BB 12) was analysed. Four types of samples were prepared: (1) fermented milk inoculated with Lactobacillus acidophilus LA 5, (2) fermented milk inoculated with Bifidobacterium bifidum BB 12, (3) fermented milk produced from milk previously treated with mTGase and inoculated with Lactobacillus acidophilus LA 5, (4) and fermented milk produced from milk previously treated with mTGase and inoculated with Bifidobacterium bifidum strain BB 12. The samples were analysed after the 1st, 7th and 14th day of storage at 5 ± 1°C. It has been found that the use of microbial transglutaminase for the production of fermented milk inoculated with monoculture affected its viscosity, hardness, acetaldehyde content and increased the viability of probiotic bacteria. The enzyme activity resulted in an significant decrease in the titratable acidity of the experimental products, positively affected viscosity, the viability of probiotic bacteria and the organoleptic properties of fermented milk.